Functional Diversity: An Epistemic Roadmap. (4th September 2019) - Malaterre, Christophe; Dussault, Antoine C; Mermans, Ely; Barker, Gillian; Beisner, Beatrix E; Bouchard, Frédéric; Desjardins, Eric; Handa, I Tanya; Kembel, Steven W; Lajoie, Geneviève; Maris, Virginie; Munson, Alison D; et al.
Abstract: Functional diversity holds the promise of understanding ecosystems in ways unattainable by taxonomic diversity studies. Underlying this promise is the intuition that investigating the diversity of what organisms actually do (i.e., their functional traits) within ecosystems will generate more reliable insights into the ways these ecosystems behave, compared to considering only species diversity. But this promise also rests on several conceptual and methodological (i.e., epistemic) assumptions that cut across various theories and domains of ecology. These assumptions should be clearly addressed, notably for the sake of an effective comparison and integration across domains, and for assessing whether or not to use functional diversity approaches for developing ecological management strategies. The objective of this contribution is to identify and critically analyze the most salient of these assumptions. To this aim, we provide an epistemic roadmap that pinpoints these assumptions along a set of historical, conceptual, empirical, theoretical, and normative dimensions.